2000
DOI: 10.2486/indhealth.38.339
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Renal Dysfunction and Bone Metabolism Disorder in Male Rats after Long-Term Oral Quantitative Cadmium Administration.

Abstract: To investigate the importance of the cadmium (Cd) exposure condition in the evaluation of toxic effect on renal function and bone metabolism, six groups of Male Wistar rats were given Cd at respective daily doses of 2, 5, 10, 20, 30 and 60 mgCd/kg (as CdCl 2 ) via a gastric tube for 6 consecutive days a week for 60 weeks. In the groups given a low Cd dose (2, 5 and 10 mgCd/kg), relatively more Cd accumulated in the kidney without liver damage than in the liver. In the high Cd dose groups (20, 30 and 60 mgCd/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 60 publications
1
35
0
Order By: Relevance
“…We also referred to an experimental study of long-term oral Cd administration in rats (Ohta et al, 2000). Based upon these studies, we determined that an oral Cd dose of 1 mg/kg would be similar to the daily level of Cd intake in humans.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also referred to an experimental study of long-term oral Cd administration in rats (Ohta et al, 2000). Based upon these studies, we determined that an oral Cd dose of 1 mg/kg would be similar to the daily level of Cd intake in humans.…”
Section: Resultsmentioning
confidence: 99%
“…In laboratory animals, renal damage and osteoporosis are the major adverse health effects associated with exposure to low levels of Cd (Brzoska and Moniuszko-Jakoniuk, 2004;Honda et al, 2003;Ohta et al, 2000). Metallothionein (MT) is a metal-binding protein that regulates the homeostasis of biologically essential metals and is also involved in the absorption, transportation, and accumulation of heavy metals such as Cd.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic intake of Cd in food or in air produces organ dysfunction as a result of cell death (3). Cd is widely used in pigments, plastic stabilizers, electroplating, alloys, nickel-Cd batteries, and welding in industry and is also present in tobacco (4,5). Natural sources of Cd are spread into the atmosphere by volcanic activity, forest fires, and wind-blown transport of soil particles.…”
Section: Introductionmentioning
confidence: 99%
“…The PVDF membrane was incubated with 0.5 % skim milk in TBS (pH 8.0) containing 0.05 % Tween 20 (Tween-TBS) and subsequently incubated overnight with rabbit anti-metal-binding protein primary antibody. The primary antibody used recognizes rat MT, and was the same antibody used in a previously reported study (Ohta et al, 2000). After washing with Tween-TBS, the membrane was incubated with an alkaline phosphatase-conjugated secondary antibody for 90 min.…”
Section: Sds-page and Immunoblottingmentioning
confidence: 99%
“…Cd is present in food or water, and accumulates in human or animal tissues especially the liver and kidney. It has been reported that exposure to low levels of Cd may result in renal damage and osteoporosis, which are considered to be the major adverse health effects of Cd exposure in laboratory animals (Brzoska and Moniuszko-Jakoniuk, 2004;Honda et al, 2003;Ohta et al, 2000).…”
Section: Introductionmentioning
confidence: 99%